DRD4 Rare Variants in Attention-Deficit/Hyperactivity Disorder (ADHD): Further Evidence from a Birth Cohort Study - Tovo-Rodrigues, Luciana; Rohde, Luis A.; Menezes, Ana M. B.; Polanczyk, Guilherme V.; Kieling, Christian; Genro, Julia P.; Anselmi, Luciana; Hutz, Mara H. (PloS one, 2013)
The dopamine receptor D4 (DRD4) is one of the most studied candidate genes for Attention-Deficit/Hyperactivity Disorder (ADHD). An excess of rare variants and non-synonymous mutations in the VNTR region of 7R allele in ADHD subjects was observed in previous studies with clinical samples. We hypothesize that genetic heterogeneity in the VNTR is an important factor in the pathophysiology of ADHD. The subjects included in the present study are members of the 1993 Pelotas Birth Cohort Study (N=5,249). We conducted an association study with the 4,101 subjects who had DNA samples collected. The hyperactivity-inattention scores were assessed through the parent version of the Strengths and Difficulties Questionnaire at 11 and 15 years of age. The contribution of allele's length and rare variants to high hyperactivity/inattention scores predisposition was evaluated by multivariate logistic regression. No effect of allele length was observed on high scores of hyperactivity-inattention. By contrast, when resequencing/haplotyping was conducted in a subsample, all 7R rare variants as well as non-synonymous 7R rare variants were associated with high hyperactivity/inattention scores (OR=2.561; P=0.024 and OR=3.216; P=0.008 respectively). A trend for association was observed with 4R rare variants. New coding mutations covered 10 novel motifs and many of them are previously unreported deletions leading to different stop codons. Our findings suggest a contribution of DRD4 7R rare variants to high hyperactivity-inattention scores in a population-based sample from a large birth cohort. These findings provide further evidence for an effect of DRD4 7R rare variants and allelic heterogeneity in ADHD genetic susceptibility.